Reproducibility of performance in three types of training test in swimming - Alberty, M.; Sidney, M.; Huot-Marchand, F.; Dekerle, J.; Bosquet, L.; Gorce, P.; Lensel, G. (International Journal of Sports Medicine, 2006)
A variety of testing procedures are used to assess the effects of particular treatments on the training status of athletes. The present study aims to investigate the reproducibility of selected tests in swimming. Sixteen trained swimmers performed three kinds of test: 1) Constant Distance Test (CDT), 2) Constant Time Test (CTT), and 3) Constant Velocity Test (CVT). The analysis of the reproducibility was based on a test-retest procedure. The test-retest performances were highly correlated for the three kinds of test (r = 0.98, 0.98, and 0.93 for CDT, CTT and CVT, respectively). The mean Coefficient of Variation (CV) was computed between test-retest for each subject and each procedure. A repeated measures one-way ANOVA showed that CVT was significantly less reliable (CV = 6.46 ± 6.24 %) than CDT and CTT (CV = 0.56 ± 0.60 % and 0.63 ± 0.54 % respectively) (p < 0.001). Psychological factors and a lack of familiarity with CVT (not extensively used during training session) could explain its greater variability. Thus, CDT and CTT seem to be the most reliable tests to detect the smallest meaningful change in the training status of swimmers. Post-hoc power calculations of the experimental design showed the sample size would have to increase to 80, 113, and 228 subjects for CWT, CDT and CPT respectively, to reach a power of 80 %. The minimal detectable differences have to be calculated to ensure a real effect of a particular treatment on a group of swimmers, according to the kind of test used.